2005
DOI: 10.1242/jeb.01486
|View full text |Cite
|
Sign up to set email alerts
|

In vivomuscle functionvsspeed I. Muscle strain in relation to length change of the muscle-tendon unit

Abstract: differences in their architecture and the kinematic patterns of the associated joints, these two joint extensors exhibited similar activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 56 publications
4
53
1
1
Order By: Relevance
“…Because EMG activity of this muscle was measured using fine-wire electrodes, this disparity may be due to differences in electrode placement. Other studies have shown that the TRILAT activates during late swing and deactivates anywhere from early stance to mid-stance (Hoyt et al, 2005;Robert et al, 2002). The SUP and INF have previously been shown to activate from early to mid-stance and to deactivate in late stance during walking, trotting and cantering (Aoki et al, 1984).…”
Section: Comparison With Literature Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Because EMG activity of this muscle was measured using fine-wire electrodes, this disparity may be due to differences in electrode placement. Other studies have shown that the TRILAT activates during late swing and deactivates anywhere from early stance to mid-stance (Hoyt et al, 2005;Robert et al, 2002). The SUP and INF have previously been shown to activate from early to mid-stance and to deactivate in late stance during walking, trotting and cantering (Aoki et al, 1984).…”
Section: Comparison With Literature Studiesmentioning
confidence: 97%
“…Loading of the passive structures of the distal forelimb has been the subject of frequent study (Biewener, 1998;Harrison et al, 2010;Jansen et al, 1993;Meershoek et al, 2001;Swanstrom et al, 2004;Swanstrom et al, 2005;Wilson et al, 2001); however, little is known about the coordination of active muscle contraction (Butcher et al, 2009;Hoyt et al, 2005;Jansen et al, 1992;Tokuriki et al, 1989). Muscle activation patterns have been predicted from calculations of net joint torques using biomechanical models of the forelimb (Harrison et al, 2010;Swanstrom et al, 2005;Wilson et al, 2001), but no study has validated these calculations against direct measurements obtained in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active lengthening during knee flexion in early stance may be functionally similar to that seen in the single joint vastus lateralis of quadrupedal mammals and the femerotibialis of birds (Gillis and Biewener, 2001;Gillis et al, 2005;Hoyt et al, 2005;Roberts et al, 2007). Active lengthening of fascicles in the knee extensors of humans may also occur during stance knee flexion (Cutts, 1989), but in vivo data on this point are lacking.…”
Section: Function Of the Active Lengthening-shortening Cycle In The Ilpomentioning
confidence: 98%
“…Conservation of energy is key in organismal ecology, and likely a substrate upon which selection acts (Weibel et al, 1998;Koteja et al, 1999). Therefore, the intensity with which limb muscles are recruited is expected to vary with locomotor demand: for example, in terrestrial locomotion, increases in speed on the level and uphill are associated with intensified recruitment of limb extensors (Gillis and Biewener, 2001;Gillis et al, 2005;Hoyt et al, 2005;Crook et al, 2010). In fluid-based locomotion, however, the relationship between muscle recruitment intensity and the speed of flight or swimming is not expected to be linear; flapping flight, for instance, is expected to require more power at extreme than intermediate speeds due to the requirements of producing lift at low speeds and overcoming parasite and profile drag at high speeds (Pennycuick, 1968a;Rayner, 1979).…”
Section: Introductionmentioning
confidence: 99%